Brodalumab: Six-Year US Pharmacovigilance Report - Mark G. Lebwohl; John Y. Koo; April W. Armstrong; Bruce E. Strober; Soo Han Yoon; Nicole N. Rawnsley; Earl L. Goehring; Gina D. Mangin; Abby A. Jacobson (Dermatology and Therapy)
Abstract Introduction Brodalumab is a human interleukin-17 receptor A antagonist indicated for the treatment of moderate-to-severe plaque psoriasis in adult patients who are candidates for systemic therapy or phototherapy and have failed to respond or have lost response to other systemic therapies. In the USA, brodalumab has a boxed warning regarding suicidal ideation and behavior and is only available under a Risk Evaluation and Mitigation Strategy, but no causal association has been established. To assess long-term safety of brodalumab, we summarize pharmacovigilance data from 6 years of real-world clinical practice. Methods Crude adverse event (AE) reporting rates per 100 patients were calculated for common AEs and AEs of special interest reported to Ortho Dermatologics by US patients and healthcare providers from August 15, 2017 through August 14, 2023. Brodalumab exposure was estimated as time from the first to last prescription-dispensing authorization dates. Adverse events were defined by Medical Dictionary for Regulatory Activities v26.0 Preferred Terms and standardized MedDRA queries. Results Data were collected from 5138 US patients (estimated exposure of 6900 patient-years). Over 6 years, 13 cases of adjudicated major adverse cardiovascular events were reported (0.25 events/100 patients). The rate of serious infections was 2.20 events/100 patients. Since the 5-year report, there was one new case of Candida infection and a serious fungal infection of the elbow. Among 57 reported malignancies affecting 49 patients, 4 were deemed possibly related to brodalumab. One new case of indeterminate inflammatory bowel disease unrelated to brodalumab was reported. No new suicide attempts were reported in year 6, and there were no completed suicides throughout 6 years. Conclusion Pharmacovigilance data throughout 6 years are consistent with the safety profile of brodalumab established in clinical trials and previous US pharmacovigilance reports, with no completed suicides and a low fungal infection rate. Graphical Abstract